Preoperative immunological plasma markers TRAIL, CSF1 and TIE2 predict survival after resection for biliary tract cancer - Jansson, Hannes; Cornillet, Martin; Sun, Dan; Filipovic, Iva; Sturesson, Christian; O’Rourke, Colm J.; Andersen, Jesper B.; Björkström, Niklas K.; Sparrelid, Ernesto (Frontiers in Oncology, 2023)
Systemic inflammatory markers have been validated as prognostic factors for patients with biliary tract cancer (BTC). The aim of this study was to evaluate specific immunologic prognostic markers and immune responses by analyzing preoperative plasma samples from a large prospectively collected biobank. Expression of 92 proteins representing adaptive and innate immune responses was investigated in plasma from 102 patients undergoing resection for BTC 2009-2017 (perihilar cholangiocarcinoma n=46, intrahepatic cholangiocarcinoma n=27, gallbladder cancer n=29), by means of a high-throughput multiplexed immunoassay. Association with overall survival was analyzed by Cox regression, with internal validation and calibration. Tumor tissue bulk and single-cell gene expression of identified markers and receptors/ligands was analyzed in external cohorts. Three preoperative plasma markers were independently associated with survival: TRAIL, TIE2 and CSF1, with hazard ratios (95% confidence intervals) 0.30 (0.16-0.56), 2.78 (1.20-6.48) and 4.02 (1.40-11.59) respectively. The discrimination of a preoperative prognostic model with the three plasma markers was assessed with concordance-index 0.70, while the concordance-index of a postoperative model with histopathological staging was 0.66. Accounting for subgroup differences, prognostic factors were assessed for each type of BTC. TRAIL and CSF1 were prognostic factors in intrahepatic cholangiocarcinoma. In independent cohorts, TRAIL-receptor expression was higher in tumor tissue and seen in malignant cells, with TRAIL and CSF1 expressed by intra- and peritumoral immune cells. Intratumoral TRAIL-activity was decreased compared to peritumoral immune cells, while CSF1-activity was increased. The highest CSF1 activity was seen in intratumoral macrophages, while the highest TRAIL-activity was seen in peritumoral T-cells. In conclusion, three preoperative immunological plasma markers were prognostic for survival after surgery for BTC, providing good discrimination, even compared to postoperative pathology. TRAIL and CSF1, prognostic factors in intrahepatic cholangiocarcinoma, showed marked differences in expression and activity between intra- and peritumoral immune cells.